2020
DOI: 10.31234/osf.io/28vsj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 exposes enduring inequalities for children & families

Abstract: As a call to action in the field, we highlight that the COVID-19 pandemic is an abrupt and chronic stressor to children and families of disadvantaged and marginalized backgrounds. Critically, this global crisis has a disproportionate impact on the physical, mental and behavioral health of these vulnerable members of society, due to pre-existing disadvantages such as economic hardship, educational inequities, risks of maltreatment and community violence. A lack of access to mental health support further deprive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The pandemic exacerbated inequalities (Condon et al, 2020;Pirtle, 2020;C. Walsh, 2020), and marginalized students were most affected (Burgess & Sievertsen, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic exacerbated inequalities (Condon et al, 2020;Pirtle, 2020;C. Walsh, 2020), and marginalized students were most affected (Burgess & Sievertsen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study builds on the scholarship on COVID-19, which has found a disproportionate, negative impact on marginalized populations (Gupta et al, 2020; Haffajee & Mello, 2020; Hale et al, 2020; Kim et al, 2020; Singh & Singh, 2020; van Dorn et al, 2020). The virus exacerbated preexisting inequalities (Condon et al, 2020; Robinson et al, 2020). Though research has yet to document the long-term impact of COVID-19, researchers have long documented how inequality inhibits marginalized students’ success (Greenwald et al, 1996; Hanushek & Woessmann, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The very policies implemented to thwart the spread of the virus have placed families at heightened risk for violence exposure and child maltreatment. Increased unemployment, housing instability, disruptions in routine, lack of childcare, quarantine, infection, and stress associated with systemic racism and inequities, have created a hotbed for conflict in the home (Buttell & Ferreira, 2020;Condon et al, 2020;Grasso, Briggs-Gowan et al, 2021;Holmes et al, 2020). On surveys, about one in five individuals have reported an increase in verbal or physical conflict with a partner during the pandemic, and this corresponds to greater alcohol and substance use, increased child and adult emotional and behavioral problems, and cumulative pandemic-related stressors (Grasso, Briggs-Gowan et al, 2021;Grasso, Lewin, et al, 2021).…”
mentioning
confidence: 99%
“…The early version of the manuscript has previously appeared online as a preprint at Condon et al ( 2020 ). All authors are members of the Yale Early Stress and Adversity Consortium.…”
mentioning
confidence: 99%